The Inhibitory Power Extract Of Balsamica Plant (Impatiens balsamica L) on Aeromonas hydrophila Bacteria Growth - Galih Arif Kusuma; Sammy N. J. Longdong; Reiny A. Tumbol (Sam Ratulangi University, 2014)
This research aimed to assess the potential use of extracts of leaves, flowers, and stems of the balsamica plant increase inhibitory effect on the growth of Aeromonas hydrophila. The content of the plant contains a compound balsamica naphthoquinone, coumarin derivatives, tannins, flavonoids, and steroids. The active compounds have the ability as an antimicrobial. A hidrophyla bacteria, including opportunistic pathogens are almost always found in water and often cause disease when the fish in adverse conditions. Antibacterial activity test in this research using the spread plate method. Data obtained in the form of the extract, the results of bacterial inoculation, and the inhibition test results, will be analyzed, displayed with pictures and described descriptively. The result of the process of maceration extraction using ethanol 70% was obtained three extracts are concentrated leaf extract: 28.75 g, flower: 12.82 g, and rods: 29.48 g. The result of antibacterial extracts of leaves, stems, and flowers balsamica plant showed inhibitory activity on the A hydrophila bacteria that seems to be indicated by a clear zone around the paper disc. Based on the classification of leaf extract and extract of the stem can be classified in the class of strong, because the inhibition zone formed by the leaf extract is equal to 11.2 mm, and extract stem with 13.7 mm inhibition zone. Ability flower extract in inhibiting the growth of A hidrophila bacteria with 21.4 mm inhibition zone showed that the extract was included in a very strong class. Keywords: The ethanol extract balsamica, Impatiens balsamica L, Aeromonas hydrophila, antibacterial activity test.